Effect of Ajwa Dates Consumption to Inhibit the Progression of Preeclampsia Threats on Mean Arterial Pressure and Roll-Over Test. (10th December 2019) - Royani, Ida; As'ad, Suryani; Mappaware, Nasrudin A; Hatta, Mochammad; Rabia,
Abstract : Background . Preeclampsia is the major problem and the main leading cause of fetal and maternal mortality worldwide. The early prediction of preeclampsia in pregnant women is required to prevent the occurrence of preeclampsia. The mean arterial pressure (MAP) and roll-over test (ROT) are the combination of measurement which can be used to predict preeclampsia. On the contrary, Ajwa dates were reported to have an enormous activity which contributes to its role in improving health conditions. In this study, we aimed to evaluate the effect of daily consumption of seven Ajwa dates on prevention of preeclampsia, through MAP and ROT changes. Methods . Forty pregnant women ( n  = 40) were randomly assigned into the control group ( n  = 10) and the intervention group which received a daily intake of Ajwa dates ( n  = 30). The MAP and ROT were assessed before and after the 8-week intervention period. Results . The intervention group showed the significant reduction in MAP and ROT following the 8-week intervention period (p < 0.05 ). Conclusion . Daily consumption of seven Ajwa dates has a remarkable potential to decrease the MAP and ROT in pregnant women at risk of developing preeclampsia, and thus, it can contribute to prevent the development of preeclampsia.